Efficacy of a telerehabilitation intervention programme using biofeedback among computer operators. - Golebowicz, Merav; Levanon, Yafa; Palti, Ram; Ratzon, Navah Z. (Ergonomics, 2015)
Computer operators spend long periods of time sitting in a static posture at computer workstations and therefore have an increased exposure to work-related musculoskeletal disorders (WRMSD). The present study is aimed at investigating the feasibility and effectiveness of a tele-biofeedback ergonomic intervention programme among computer operators suffering from WRMSD. Twelve subjects with WRMSD were assigned an ergonomic intervention accompanied by remote tele-biofeedback training, which was practised at their workstations. Evaluations of pain symptoms and locations, body posture and psychosocial characteristics were carried out before and after the intervention in the workplace. The hypothesis was partially verified as it showed improved body position at the workstation and decreased pain in some body parts. Tele-biofeedback, as part of an intervention, appears to be feasible and efficient for computer operators who suffer from WRMSD. This study encourages further research on tele-health within the scope of occupational therapy practice. Practitioner Summary:Research concerning tele-health using biofeedback is scarce. The present study analyses the feasibility and partial effectiveness of a tele-biofeedback ergonomic intervention programme for computer operators suffering from WRMSD. The uniqueness and singularity of this study is the usage of remote communication between participants and practitioners through the Internet.